Implementation of Antibiotic Stewardship: A South Indian Experience. (4th October 2017) - Singh, Sanjeev; Menon, Vidya; Kumar, Anil; Nampoothiri, Vrinda; Mohamed, Zubair Umer; Sudhir, Sangita; Pogue, Jason; Kaye, Keith S; Patel, Payal
Abstract: Background: Access to antimicrobials in India is unregulated. Retail data confirms antibiotic prescriptions have escalated in the last decade, contributing to antimicrobial resistance. Antimicrobial stewardship programs (ASP) are rare in India but, with government support, are gaining momentums. We describe implementation of an ASP in a 1, 300-bed, private, tertiary-care center in India in Southern India. Methods: An ASP was established in Feb 2016 consisting of an administrative champion, hospitalist, microbiologist, intensivist and 5 pharmacists. Daily post-prescriptive review of targeted antimicrobials was done, including polymyxins, carbapenems, tigecycline, and linezolid. Institutional guidelines for polymyxins were created and disseminated. Socioadaptive strategies included promoting culture change and empowering pharmacist champions. The ASP evaluated and tracked the appropriateness of antimicrobial administration, including loading and maintenance dose, frequency, route, duration of therapy, de-escalation and compliance with ASP recommendations. Economic impact of ASP post implementation (February –July 2016) was compared with a pre-implementation period (August 2015–January 2016). Results: In the post implementation period, 868 patients were prescribed targeted antibiotics. Fifty-one percent (442) prescriptions required adjustment for drug selection, route, dose, or duration. Loading dose was indicated but not prescribed in 31% (266) of prescriptions, 14% (118) had inappropriate maintenance dose and 13% (110) were continued beyond standard recommended durations. Compliance was noted with 50% of ASP recommendations. Departments with high compliance rates included Neurosurgery (63%), Urology (62%), and Medicine (59%). Significant decreases in cost (Figure 1) were noted for ertapenem (Rs 106200 reduced to Rs 15930), colistin (Rs 1368258 to Rs 338322) and linezolid (Rs 919296 to Rs 137472) (all P  < 0.05) (1USD~64 Rs). Utilization of Colistin and Linezolid decreased from 422 vials to 94 (22%) and 1320 vials to 202 (15%), respectively. Conclusion: Preliminary results of an ASP in a large Indian hospital are encouraging. Potential antibiotic and department-specific targets for advanced stewardship interventions were identified. Disclosures: K. S. Kaye, Xellia: Consultant, Consulting fee. Merck: Consultant and Grant Investigator, Consulting fee and Research support. The Medicines Company: Consultant and Grant Investigator, Consulting fee and Research support.